The Influence of Business, Technology and HR Transformation Strategies on ESG (Environmental, Social & Governance) Performance in the Indonesian Energy Industry - Rivanodi, Rivanodi; Noviaristanti , Siska (Publisher Cv. Inara, 2025)
This study aims to investigate the influence of business transformation strategies, technology and HR on ESG (Environmental, Social & Governance) performance in the energy industry in Indonesia. With the background of awareness of the importance of maintaining long-term company stability, companies are now focusing on business actions that can coexist with the environment and provide positive social impacts. Through a quantitative approach, this study assesses the relationship between transformation strategies and ESG performance, as well as their impact on companies and stakeholders. This study uses secondary data with a research population of companies in the energy sector listed on the IDX. Sample selection was carried out using the purposive sampling judgment method. This approach uses the SEM research model using smartPLS software in data management. The results of the study indicate that the construct of the three transformation strategies, namely technology and HR, can improve ESG performance through the role of business transformation as a connecting moderator. By focusing on these three aspects, the company is expected to optimize ESG performance while simultaneously creating long-term positive impacts for the environment and society.